“Siapa Pappus of Alexandria?” Analisis Pengetahuan Mahasiswa Prodi Pendidikan Matematika Tentang Pappus of Alexandria - Yulyanti Harisman; Reasty Amanda; Lukman Harun (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
Mathematics is necessary because it has a vital role in civilization. Mathematicians from various nations carried out the development and renewal of mathematics. We must know the mathematicians who played a role in the development and regeneration of mathematics and the theorems they left behind. Pappus of Alexandria is one of the mathematicians who had an essential role in reforming mathematics. Therefore, this research is conducted with the aim that readers can recognize who Pappus of Alexandria is and his findings. The type of research conducted in this writing is qualitative with case study and literature review methods, while the instrument used in this research is an open interview. A literature review was conducted by reviewing articles to obtain Pappus's biography and findings. In contrast, the case study was conducted by selecting ten students as research subjects from the mathematics education program. The results of this study show that there are three categories of students' knowledge about Pappus of Alexandria and his theorems.